High Achiever : The Incredible True Story of One Addicts Double Life - Jenkins, Tiffany (Motivational speaker) (New York : Harmony Books, 2019)
"When word got out that Tiffany Jenkins was withdrawing from opiates on the floor of a jail cell, people in her town were shocked. Not because of the twenty felonies shed committed, or the nature of her crimes, or even that shed been captain of the high school cheerleading squad just a few years earlier, but because her boyfriend was a Deputy Sherriff, and his friends--their friends--were the ones whod arrested her. A raw and twisty page-turning memoir that reads like fiction, High Achiever spans Tiffanys life as an active opioid addict, her 120 days in a Florida jail where every officer despised what shed done to their brother in blue, and her eventual recovery. With heart-racing urgency and unflinching honesty, Jenkins takes you inside the grips of addiction and the desperate decisions it breeds. She is a born storyteller who lived an incredible story, from blackmail by an ex-boyfriend to a soul-shattering deal with a drug dealer, and her telling brims with suspense and unexpected wit. But the true surprise is her path to recovery. Tiffany breaks through the stigma and silence to offer hope and inspiration to anyone battling the disease--whether its a loved one or themselves."--Back cover.
Previously published in 2017 by the author.
Keywords: Jenkins, Tiffany -- (Motivational speaker); Drug addicts -- Biography; Drug abuse -- Treatment; Drug addiction -- Treatment; Addicts -- Rehabilitation; Autobiographies